2005
DOI: 10.1074/jbc.m410973200
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Mapping Identifies Hotspot Site of Modification in Human Serum Albumin by Methylglyoxal Involved in Ligand Binding and Esterase Activity

Abstract: Methylglyoxal is a potent glycating agent under physiological conditions. Human serum albumin is modified by methylglyoxal in vivo. The glycation adducts formed and structural and functional changes induced by methylglyoxal modification have not been fully disclosed. Methylglyoxal reacted with human serum albumin under physiological conditions to form mainly the hydroimidazolone N ␦ -(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine (92% of total modification) with a minor formation of argpyrimidine, N ⑀ -(1-carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
264
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 279 publications
(285 citation statements)
references
References 41 publications
19
264
2
Order By: Relevance
“…In diabetic patients, the largest quantitative increases in protein glycation adduct residues of plasma protein occurred for MG-H1 and 3DG-H. The major site of MG-H1 residue formation in human serum albumin was identified recently as arg-410 [27]. The lack of increase in CML residues in the plasma protein of diabetic patients was unexpected and discordant with the prior report by Schleicher et al [28], who found increased CML residue concentration.…”
Section: Discussionsupporting
confidence: 68%
“…In diabetic patients, the largest quantitative increases in protein glycation adduct residues of plasma protein occurred for MG-H1 and 3DG-H. The major site of MG-H1 residue formation in human serum albumin was identified recently as arg-410 [27]. The lack of increase in CML residues in the plasma protein of diabetic patients was unexpected and discordant with the prior report by Schleicher et al [28], who found increased CML residue concentration.…”
Section: Discussionsupporting
confidence: 68%
“…The specific labeling of one tyrosine in a molecule that contains 18 tyrosines suggests that Tyr 411 is in a special environment. This tyrosine has an unusually low pKa of 7.9-8.3 (Means and Wu, 1979;Ahmed et al, 2005), in contrast to the pKa of 10 for the average tyrosine.…”
Section: Mechanism Of Op Labeling Of Albuminmentioning
confidence: 80%
“…residues, an advanced glycation end product (AGE) (17,18), with loss of associated side chain positive charge (19) (Fig. 1B).…”
Section: N␦-(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine (Mg-h1)mentioning
confidence: 99%
“…Increased concentration of MG-H1 residues in plasma protein of diabetic patients was not linked directly to A1C (22), probably because methylglyoxal formation is increased in both fasting and postprandial hyperglycemia (16,23) and influenced by factors other than hyperglycemia (low glyceraldehyde-3-phosphate dehydrogenase activity [24]). MG-H1 residue formation occurred at susceptible hotspot sites in proteins with loss of functional activity (19). The surface sheath network of type IV collagen in blood vessels (25) binds integrins of vascular endothelial cells, anchoring and sustaining the vascular endothelium by interaction with integrins at GFOGER and RGD sites of the triple helical domain (9,26).…”
Section: N␦-(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine (Mg-h1)mentioning
confidence: 99%